2008
DOI: 10.1080/13803390701336866
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition and facilitation in schizotypy

Abstract: Participants scoring high and low on a schizotypy scale (n=18 in each group) switched between naming words and naming colors in a Stroop task in congruent, neutral, and incongruent conditions. The findings were that, while being slower and less accurate overall than low schizotypes, the high schizotypy group did not display disproportionately greater Stroop inhibition or facilitation, suggesting intact selective attention. However, the high schizotypy group suffered disproportionately larger switching costs. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…Our findings of associations between positive, cognitive, and asocial schizotypal traits and impairments in inhibition and cognitive flexibility or attentional switching (Color–Word Interference Test) are in line with past studies that have found high schizotypes to display greater inhibitory latency and less accurate responses compared with low schizotypes on all inhibition and switching conditions of the Color–Word Interference Test ( 12 ). These findings are also in line with recent schizophrenia research, which has revealed inhibitory deficits using the Color–Word Interference Test ( 30 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings of associations between positive, cognitive, and asocial schizotypal traits and impairments in inhibition and cognitive flexibility or attentional switching (Color–Word Interference Test) are in line with past studies that have found high schizotypes to display greater inhibitory latency and less accurate responses compared with low schizotypes on all inhibition and switching conditions of the Color–Word Interference Test ( 12 ). These findings are also in line with recent schizophrenia research, which has revealed inhibitory deficits using the Color–Word Interference Test ( 30 ).…”
Section: Discussionsupporting
confidence: 92%
“…Poorer neurocognitive performance similar to that seen in schizophrenia, albeit in a milder form, has been identified in individuals exhibiting high levels of schizotypy traits ( 11 ). For example, inferior levels of attention and executive functioning have been revealed: Cimino and Haywood ( 12 ) found healthy individuals high in schizotypy traits, based on a mean of all Oxford–Liverpool Inventory of Feelings and Experiences (O-LIFE; a self-report inventory assessing schizotypy) factor scores, to exhibit significantly more errors and longer latencies on the Stroop Color–Word Interference Test, in comparison with individuals low in schizotypal traits. This finding is indicative of relative impairments in inhibition and attentional switching or cognitive flexibility ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies support the argument that high schizotypy and impaired inhibition are connected (Cimino and Haywood, 2008), particularly in cases of positive schizotypy (Louise et al, 2015). Impaired cognitive flexibility (as measured by the trail-making test or the Wisconsin Card Sorting Test) has been associated with the negative dimension of schizotypy (Louise et al, 2015; for a review see Giakoumaki, 2012).…”
Section: Introductionmentioning
confidence: 84%
“…For example, relatively inconsistent findings are observed in the negative priming paradigm (89, 119) and the Stroop task (89, 120126). Additionally, Raine (41) argues that the level of general intelligence is relatively unimpaired in schizotypy.…”
Section: Genetic Cognitive and Neurobiological Studies Of Schizotypmentioning
confidence: 99%